Bacterial Nucleoid-Associated Protein Uncouples Transcription Levels from Transcription Timing - Igor Zwir (American Society for Microbiology, 2014)
ABSTRACT The histone-like nucleoid-structuring (H-NS) protein binds to horizontally acquired genes in the bacterium Salmonella enterica serovar Typhimurium, silencing their expression. We now report that overcoming the silencing effects of H-NS imposes a delay in the expression of genes activated by the transcriptional regulator PhoP. We determine that PhoP-activated genes ancestral to Salmonella are expressed before those acquired horizontally. This expression timing reflects the in vivo occupancy of the corresponding promoters by the PhoP protein. These results are surprising because some of these horizontally acquired genes reached higher mRNA levels than ancestral genes expressed earlier and were transcribed from promoters harboring PhoP-binding sites with higher in vitro affinity for the PhoP protein. Our findings challenge the often-made assumption that for genes coregulated by a given transcription factor, early genes are transcribed to higher mRNA levels than those transcribed at later times. Moreover, they provide a singular example of how gene ancestry can impact expression timing. IMPORTANCE We report that gene ancestry dictates the expression behavior of genes under the direct control of the Salmonella transcriptional regulator PhoP. That is, ancestral genes are transcribed before horizontally acquired genes. This reflects both the need to overcome silencing by the H-NS protein of the latter genes and the architecture of the corresponding promoters. Unexpectedly, transcription levels do not reflect transcription timing. Our results illustrate how a bacterium can exhibit an elaborate temporal expression behavior among genes coregulated by a transcription factor even though the products encoded by the target genes do not participate in a morphological or developmental pathway.